SELECTION OF VARIETIES AND SAMPLES OF FORAGE LEGUM CROP (VICIA FABA L.) BY THE CONTENT OF CHLOROPHYLL IN THE LEAVES - S. T. Jo‘rayev; M.B. Jumanova (Modern American Journals, 2026)
The article presents a scientifically substantiated analysis of the number of chlorophyll grains on the leaf surface of plants during the formation periods of 25 varieties and samples of broad bean (Vicia faba L.) from the world collection in the studied control nursery.
Keywords: Southern region, SPAD-502, nursery, variety, line, leaf surface, soil, biomass.